Composition of venezuelan lemon essential oil Citrus limon (L.) Burm.f. - Ojeda de Rodríguez, G.; Morales de Godoy, V.; González de Colmenares, N.; Cabrera Salas, L.; Sulbaran de Ferrer, B. (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2012)
The essential oil composition from fruit peels of C. limon grown in Zulia State (Venezuela), is reported. A total of 51 constituents were identified and quantified by HRGC and GC-MS, using an interna1 standard and response factor. The major prominent constituent was limonene (65,65%) and the main aldehydes were geranial(1,43%) and neral(0,87%).